Hellboy and the B.P.R.D. 1957 - Mignola, Mike; Roberson, Chris (Dark Horse Books, 2023)
"Hellboy crisscross the globe on missions to track down demonic books, solve the sightings of mysterious creatures, and deal with restless spirits in this gripping collection of one-shots. These stories will let readers get to know some of the human members of the B.P.R.D. and the unique talents they bring to the organization. Even Hellboy needs backup from time to time!"--